AXIOLOGICAL FOUNDATIONS OF THE IMPLEMENTATION OF THE NEW UZBEKISTAN DEVELOPMENT STRATEGY - Oripov Elyor Shavkatovich ,; Inomjonov Elbek G'anijon o'g'li , (TADQIQOTLAR.UZ, 2024)
Abstract: In this article, the need to achieve harmony of traditional and modern values in the implementation of the development strategy of New Uzbekistan is scientifically and comparatively analyzed. In addition, the axiological basis of the concept of traditionalism has been researched, and its rationalist and praxeological influence on society has been studied.